Instafamous and social media influencer marketing. Issue 5 (21st March 2019) - Jin, S. Venus; Muqaddam, Aziz; Ryu, Ehri
Abstract : Purpose: The purpose of this paper is to test the effects of two types of celebrities (Instagram celebrity vs traditional celebrity) on source trustworthiness, brand attitude, envy and social presence. The proposed theoretical model consists of the celebrity type as the independent variable, social presence as the mediator and self-discrepancy as the moderator. Design/methodology/approach: A randomized two-group comparison (Instagram celebrity vs traditional celebrity) between-subjects experiment ( n =104) was conducted. Findings: The results indicate that consumers exposed to Instagram celebrity's brand posts perceive the source to be more trustworthy, show more positive attitude toward the endorsed brand, feel stronger social presence and feel more envious of the source than those consumers exposed to traditional celebrity's brand posts. Structural equation modeling (Mplus 8.0) and bootstrap confidence intervals indicate that social presence mediates the causal effects of celebrity type on trustworthiness, brand attitude and envy. Multiple regression analyses reveal the moderating effects of appearance-related actual–ideal self-discrepancy. Practical implications: Ultimately, managerial implications for social media marketing and Instagram influencer-based branding are provided. From the perspective of marketing planning, the findings speak to the power of influencer marketing as an effective branding strategy. Originality/value: The paper discusses theoretical implications for the marketing literature on celebrity endorsements.